İlaç üreticisinin cezai sorumluluğu - Baş, Enes (My University, 2023)
İlaç; Dünya Sağlık Örgütü tarafından insanı fiziksel, sosyal ve ruhsal olarak iyi olma hali şeklinde tanımlanan sağlıklı olma durumuna ulaştırmayı hedef edinen bir madde olup doğumdan ölüme kadar varlığını sürdürmektedir. Geçmişi milattan önceki yıllara ve doğada yer alan maddelere dayanan ilaç; günümüzde oldukça güçlü bir endüstriye sahiptir. İnsan nüfusuna bağlı olarak artan ihtiyaç ve gelişen teknoloji, ilaç ve ilaç üretiminin önemini giderek artırmaktadır. İlaç, kimyasal yapısı gereği insanı iyi hale getirebileceği gibi ilacın insan bedeninde ciddi kalıcı zararlara ve hatta ölüme yol açabileceğine şüphe yoktur. İlacın bu yönü, ilaç üreticilerinin cezai sorumluluklarının daha fazla tartışılması gerekliliğini beraberinde getirmektedir. Bu tezde de ilaç üreticilerinin cezai sorumlulukları, Türk Ceza Kanunu ve diğer kanun ve sair mevzuat düzenlemeleri dikkate alınmak suretiyle üretim aşaması ve üretim sonrası tüketim aşaması olarak iki döneme ayrılmak suretiyle incelenmiş, öğreti ve uygulamaya katkı sağlanmaya çalışılmıştır.

The Drug refer to a substance that aims to lead people to the state of being healthy defined by the World Health Organization as a state of physical, social and mental well-being and continues to exist from birth to death. Drug, whose history dates back the years before Christ based on the substances found in nature has a very strong industry today. The increasing need and the developing technology depending on the human population gradually increase the importance of drug and drug production. There is no doubt that the drug can make people better due to its chemical structure, and that the drug can also cause serious permanent damage to the human body and even death. This aspect of the drug brings with it the necessity of further discussion of the criminal liability of drug manufacturers. In this thesis, the criminal liability of drug manufacturers; by taking the Turkish Penal Code and other codes and other legislative regulations into consideration has been analyzed in the way of dividing the whole process into two periods as production stage and post-production consumption stage, and it has been tried to contribute to the doctrine and execution.
Keywords: Ceza hukuku; Counterfeit drug; Criminal law; Drug; Drug manufacturer; Drugs; Eczacı ve cezai sorumluluk; Fake drug; Health law; İlaç; İlaç hukuku; İlaç üreticisi; İlaçlar; Law and legislation; Pharmaceutical law; Pharmacist and criminal liability; Sağlık hukuku; Sahte ilaç; Taklit ilaç; Turkey; Türkiye; Yasa ve yasama